The research on spatial-temporal evolution and influence factors of urban resilience: A case study in the Guangzhou metropolitan area - Tang, Bo; Tan, Zechuang (Frontiers in environmental science, 2022)
Resilience city, a new concept of city sustainable development, becomes one of the important subjects of high-quality development research. Compared to the traditional urban disaster mitigation approach, resilient cities focus more on the organizational capacity and coordination within the urban systems. Taking Guangzhou metropolitan area as an instance, which is featured a highly developed economy and society and frequently happened hazards and disturbances, the paper constructs an evaluation index system from four city subsystems, including economy, society, ecology, and engineering. Meanwhile, by applying the methods of global entropy weight, variation coefficient, geographic information system, and obstacle degree model, the paper explores the time changes, space evolution, and obstacle degree factors of city resilience in the Guangzhou metropolitan area from 2010 to 2020. The research results show that: (1) There is a significant change in the time difference of city comprehensive resilience of the Guangzhou metropolitan area. The resilience of each city’s resilience subsystem has grown steadily, of which the development level of economic resilience, social resilience, and engineering resilience has been steadily improved, and ecology resilience level shows a slight decline among a steadily increasing. (2) The overall city resilience of the Guangzhou metropolitan area shows a radial pattern taking Guangzhou as the core, of which the city economy, society, and engineering resilience grades mainly show a medium and low resilience level, the ecology resilience mainly shows a medium and high resilience level, and the general performance of resilience space distribution level is high in the southeast and low in the northwest. (3) Social resilience and ecological resilience are the main driving subsystems in the early and late stages of city resilience development in Guangzhou metropolitan area during the research period, and engineering resilience is the main constraint subsystem. (4) Water and soil loss control area and population density are the main obstacle factors in the early and late stages of city resilience in the Guangzhou metropolitan area. The density of the city drainage pipeline and the total import and export volume are the basic resilience barrier factors. The paper analyzes the spatial-temporal pattern and influencing factors of city resilience in the metropolitan area from a multi-dimensional perspective, provides a new thinking and analysis framework for the management and sustainability of city resilience in the metropolitan area, and provides a reference for the coordinated development of the metropolitan area.